On the distribution of the genus Teius Merrem, 1820 (Reptilia: Squamata: Teiidae) - Cacciali, Pier; Morando, Mariana; Köhler, Gunther; Avila, Luciano (Zootaxa, 2016)
The lizard genus Teius is composed by three species: Teius teyou, T. oculatus, and T. suquiensis and is distributed in South America, east of Andes. Teius teyou and T. oculatus have wide parapatric distributions with contact zones. Teius suquiensis is present in a small range along a sympatric area of the former species. In this work we analyze the distribution of the three species of Teius across its whole geographic range, examining its relationships with climatic parameters. We based our analysis on specimens in collections and literature records. Our analysis shows that the genus Teius is distributed from central Bolivia southwards to north of Río Negro Province in northern Patagonia, Argentina. Teius teyou reaches the northernmost range limit of the genus whereas T. oculatus occupies the southernmost limit. Teius oculatus is related to open and moist environments whereas T. teyou is more adapted to xeric and forested areas. Teius suquiensis is present in xerophytic areas of Dry Chaco and Espinal. Climatic factors in the distribution of the distribution of the two widespread species show marked differences and seasonality.